Diversification of Markets and Enterprises in the Exportation of Peruvian Blueberries - Montes Ninaquispe, Jose Carlos; Lizana Guevara, Nikolays Pedro; Chavesta Paico, Sheyla Johana; Coronel Benites, Cynthia Vanessa; Chombo Jaco, José Alberto; Arias Gonzales, Hilda Paola; Morán Santamaría, Rogger Orlando (LACCEI, 2024)
The study conducted analyzed Peru’s blueberry exports, focusing on market and business diversification. A quantitative and descriptive methodology was employed. Data were collected from the National Superintendence of Customs and Tax Administration of Peru (SUNAT), and the Herfindahl-Hirschman Index (HHI) was applied to quantify diversification. Findings revealed a significant increase in exports to the United States, the United Kingdom, and the Netherlands, with a notable rise in China. However, despite growth in the diversity of destinations, a concentration in target markets was observed, with an HHI exceeding 3500 by 2023. At the business level, companies such as Camposol, Hortifrut-Perú, and Agrovision Perú showed remarkable growth, reflecting greater competitiveness and a decrease in market concentration, evidenced by an HHI below 700 in the same period. The study concludes by recommending expansion into emerging markets, especially China, the integration of sustainable agricultural practices, the development of marketing strategies tailored to each market, and the implementation of constant market monitoring. These actions could strengthen Peru’s position in the international blueberry market.